Ezetimibe mitigates DNCB-induced mouse model of eczematous dermatitis - Shallal, Amnah Muntasser; Abu-Raghif, Ahmed Rahmah; Ridha-Salman, Hayder; Al-Zheery, Worood Hameed; Al-Athari, Ali Jihad Hemid (European Journal of Clinical and Experimental Medicine, 2025)
Introduction and aim. Atopic dermatitis (AD) is a life-long inflammatory dermatosis that features dry, erythematous skin. Ezetimibe is a lipid-lowering agent with enhanced anti-inflammatory and anti-oxidative capacities. This work attempted to evaluate the anti-eczematous action of topically administered ezetimibe in a mouse prototype of 1-chloro-2,4-dinitrobenzene (DNCB)-evoked AD. To our knowledge, this is the first study to investigate the topical use of ezetimibe in an experimental model of AD. Material and methods. Thirty male Swiss albino mice were randomly allocated into five groups: healthy control, DNCB-induced model, vehicle, tacrolimus (0.1% ointment), and ezetimibe (2% ointment). Treatments were applied daily for 21 days. Clinical severity scores, total and differential leukocyte counts, histopathological changes, immunohistochemical expression of interleukin (IL)-4 and IL-13, and tissue levels of IgE, malondialdehyde (MDA), IL-17, IL-31, transforming growth factor-β (TGF-β), and tumor necrosis factor-α (TNF-α) were assessed. Results. DNCB increased dermatitis severity (EASI score 9.8±0.7 vs. 0.5±0.1 in controls, p<0.001), total leukocytes (14.2±1.6 ×10³/mL vs. 3.9±0.6 ×10³/mL, p<0.001), and IgE (356±42 ng/mL vs. 92±15 ng/mL, p<0.001). Ezetimibe treatment significantly reduced EASI scores (2.1±0.4, p<0.01 vs. DNCB), leukocytes (5.9±0.3 ×10³/mL, p<0.01 vs. DNCB), IgE (128±18 ng/mL, p<0.01 vs. DNCB), and MDA (2.3±0.4 µmol/L vs. 5.9±0.7 µmol/L in DNCB, p<0.001). Pro-inflammatory cytokines IL-4, IL-13, IL-17, IL-31, TGF-β, and TNF-α were also markedly decreased (all p<0.05), with effects comparable to tacrolimus. Conclusion. Topical ezetimibe significantly alleviated DNCB-induced AD-like lesions by reducing histopathological changes, leukocyte infiltration, IgE, oxidative stress, and key inflammatory cytokines. These findings support ezetimibe as a potential adjunctive topical therapy for immune-mediated dermatoses, warranting future clinical evaluation.